Rise of Hindu Nationalism in India: An Exploration in the Light of the Roles of Bharat Sevasram Sangha and Hindu Mahasabha - Das, Totan (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
19th-century India, especially Bengal, had seen various kinds of ideas, whether related to different strains of religious movements or many kinds of political thought. All those reform movements that were begun to reform the Hindu religion gradually led to the crystallisation of Hindu nationalism. On the other hand, this journey of Hindu nationalism was acutely influenced by many sorts of movements, like Farazi, Wahabi, Tablikh and Tanjim to reform and strengthen the position of Islam in India. Against that tense religious background, so many Hindu and Muslim religious organisations gathered momentum. This paper will go through two organisations, Bharat Sevasram Sangha and Hindu Mahasabha, to shed light on activities and complex relations.